2021
DOI: 10.1029/2021jb021758
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide Dissolution and Awaruite Formation in Continental Serpentinization Environments and Its Implications to Supporting Life

Abstract: Metal and sulfide minerals in ultramafic rocks are ideal tracers for fluid-rock interaction processes. During hydrothermal alteration of ultramafic rocks-the so-called serpentinization reaction where the primary mantle minerals olivine and pyroxene are converted to serpentine, magnetite, talc, and brucite-H 2 is produced due to ferrous iron oxidation McCollom et al., 2016). Simultaneously, H 2 can react abiogenically with CO 2 or CO to produce CH 4 and higher hydrocarbons following Fischer-Tropsch Type and Sab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(157 reference statements)
1
2
0
Order By: Relevance
“…(2018), awaruite, native copper, heazlewoodite, pentlandite, and magentite are found—in various combinations—in the serpentinite matrix of samples from a range of depths, and a corresponding range of fO 2 in borehole waters logged at the same depth (Figure 28). Similar assemblages are reported in other peridotite massis (e.g., Alt et al., 2013; de Obeso & Kelemen, 2018, 2020; Schwarzenbach et al., 2012, 2016, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…(2018), awaruite, native copper, heazlewoodite, pentlandite, and magentite are found—in various combinations—in the serpentinite matrix of samples from a range of depths, and a corresponding range of fO 2 in borehole waters logged at the same depth (Figure 28). Similar assemblages are reported in other peridotite massis (e.g., Alt et al., 2013; de Obeso & Kelemen, 2018, 2020; Schwarzenbach et al., 2012, 2016, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this observation, sulfides are barely detectable in continental serpentinite springs and PBHF, whereas the H 2 S concentration in LCHF is more in the range (0.2 to 3 mM) of that of basalt-hosted hydrothermal vents, likely owing to its setting proximal to the Mid-Atlantic Ridge and its black smokers ( 51 , 52 ). However, recent studies demonstrated the key role of sulfur-cycling in supporting microbial life in continental serpentinite-hosted systems, while potentially driven by phyla other than Epsilonproteobacteria or Betaproteobacteria ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…A supportive community of researchers has grown around these topics, embodied in part by the annual Serpentine Days conferences in Europe. This overall topic is the subject of 24 of the papers in this Special Issue (Bernasconi et al., 2021; Cook, Blank, Rietze, et al., 2021; Cook, Blank, Suzuki, et al., 2021; Cooperdock et al., 2020; de Obeso et al., 2021; Ellison et al., 2021; O. Evans et al., 2020; Hong et al., 2022; Howells et al., 2022; Katayama et al., 2020; Kelemen et al., 2021; Leong et al., 2021; Malvoisin et al., 2020; Monnin et al., 2021; Nothaft, Templeton, Boyd, et al., 2021; Nothaft, Templeton, Rhim, et al., 2021; Renard, 2021; Sabuda et al., 2021; Schwarzenbach, Vogel, et al., 2021; Schwarzenbach, Vrijmoed, et al., 2021; Templeton et al., 2021; Ternieten et al., 2021a, 2021b; Yoshida et al., 2020).…”
Section: Introductionmentioning
confidence: 99%